2003
DOI: 10.1097/01.mp.0000056986.08999.fd
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Salivary Gland Angiosarcoma: A Clinicopathologic Study of 29 Cases

Abstract: Angiosarcomas of the oral and salivary gland area are extremely rare, mostly presented as case reports. We wanted to study the clinicopathologic features of a series of oral and salivary gland angiosarcomas. Cases coded as "angiosarcoma" were retrieved from the Oral and Maxillofacial Pathology Department of the Armed Forces Institute of Pathology. Patient folders and pathology were reviewed and recorded; immunohistochemistry and follow-up were obtained. Inclusion required oral or salivary gland location, vasof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 23 publications
0
86
0
1
Order By: Relevance
“…Endothelial differentiation can be confirmed by the vascular markers CD31 and CD34. These markers are expressed in most angiosarcomas of the oral cavity [11,13] but not in squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial differentiation can be confirmed by the vascular markers CD31 and CD34. These markers are expressed in most angiosarcomas of the oral cavity [11,13] but not in squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Angiosarcoma of the oral cavity may occur in various tissues, such as oral soft tissue, minor salivary glands, and bones [2][3][4][5]. The present case occurred in the cheek soft tissue in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The present case occurred in the cheek soft tissue in the oral cavity. Fanburg-Smith et al [5] reported 22 cases of primary angiosarcoma of the oral and salivary glands. The sites of the 22 cases were tongue in 9, parotid gland in 4, lip in 4, submandibular gland in 3, and palate in 1 [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations